ENHANCED ANTIMICROBIAL ACTION OF BINARY ANTIBIOTIC NANOPARTICLES - Nurlankyzy, Nuriya (Nazarbayev University School of Sciences and Humanities, 2025)
Bacteria evolve antimicrobial resistance (AMR) faster than new antibiotics are developed which is a complex, time consuming and costly process. This study proposes binary antibiotic nanoparticles made primarily from existing antibiotics to enhance their antimicrobial effectiveness. These nanoparticles contain mixed nanocrystals co-precipitated from a cationic antibiotic, tetracycline hydrochloride, and a anionic antibiotic, sodium cefoperazone, stabilized with the surface-active polymer Poloxamer 407 and coated with one of three different types of cationic surfactants, namely, Hexadecyl trimethyl ammonium bromide (HDTAB); octadecyl trimethylammonium bromide (ODTAB) and Dodecyl trimethylammonium bromide (DOTAB). The cationic surfactant coating promotes electrostatic adhesion to the bacterial cell walls, ensuring sustained release of high local concentrations of both antibiotics into the bacteria. The antimicrobial efficacy of the binary antibiotic particles (NPs) was evaluated on Gram negative bacterial strain, Escherichia coli. It resulted in an enhanced antimicrobial efficacy compared to application of the free antibiotics at equivalent overall concentration. The nanoparticles showed low-to-moderate cytotoxicity on human cells. The fact that the binary antibiotic nanoparticles contain mostly antibiotics also benefits their application as there is no residual nanocarrier left post-use. This innovative approach to reformulating existing antibiotic in binary pairs as nano-formulation offers a promising strategy against AMR without the need for new drug discovery and development.
Keywords: type of access: embargo; nanoparticles; drug delivery; antibiotic delivery; tetracycline; cefoperazone; cationic surfactants; HDTAB; ODTAB; DOTAB; antimicrobial resistance; drug release; antimicrobial efficacy; minimum inhibitory concentration; cytotoxicity; nanopartcile-based formulation